2017
DOI: 10.1038/aps.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

IR-780-loaded polymeric micelles enhance the efficacy of photothermal therapy in treating breast cancer lymphatic metastasis in mice

Abstract: Cancer metastasis is responsible for over 90% of breast cancer-related deaths, and inhibiting lymph node metastasis is an option to treat metastatic disease. Herein, we report the use of IR-780-loaded polymeric micelles (IPMs) for effective photothermal therapy (PTT) of breast cancer lymphatic metastasis. The IPMs were nanometer-sized micelles with a mean diameter of 25.6 nm and had good stability in simulated physiological solutions. Under 808-nm laser irradiation, IPMs exhibited high heat-generating capabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Additionally, the critical micellar concentration (CMC) of the PCB-lipid was 127 µg/mL, suggesting that PCB-lipid micelles were formed at low concentration and could load hydrophobic drugs more efficiently ( Figure S3 ). The IR-780–PCB-lipid feed ratio was set to a 1:10 weight ratio, and therefore, the LC (%) and EE (%) values were obtained as 5.1 and 51.1, respectively, and they are comparatively higher than other micellar nanoparticle for IR-780 delivery [ 12 , 13 ]. The absorbance spectrum of the IR-780 dye loaded in the PCB-lipid–IR-780 NPs showed a 15-nm redshift to 803 nm, indicating that hydrophobic dye inside the micelles experienced a change in polarity and hydrophobic interactions inside the micelles; and such a redshift also demonstrated that IR-780 was efficiently loaded into the PCB-lipid micellar NPs rather than physically adsorbed onto the surface of the nanoparticles [ 7 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the critical micellar concentration (CMC) of the PCB-lipid was 127 µg/mL, suggesting that PCB-lipid micelles were formed at low concentration and could load hydrophobic drugs more efficiently ( Figure S3 ). The IR-780–PCB-lipid feed ratio was set to a 1:10 weight ratio, and therefore, the LC (%) and EE (%) values were obtained as 5.1 and 51.1, respectively, and they are comparatively higher than other micellar nanoparticle for IR-780 delivery [ 12 , 13 ]. The absorbance spectrum of the IR-780 dye loaded in the PCB-lipid–IR-780 NPs showed a 15-nm redshift to 803 nm, indicating that hydrophobic dye inside the micelles experienced a change in polarity and hydrophobic interactions inside the micelles; and such a redshift also demonstrated that IR-780 was efficiently loaded into the PCB-lipid micellar NPs rather than physically adsorbed onto the surface of the nanoparticles [ 7 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the characteristics of IR-780 iodide, such as poor water solubility, rapid clearance, and acute toxicity, limit its direct clinical use 19 , 20 . A good approach is to encapsulate IR-780 iodide in nanostructures and deliver it to tumor cells 21 23 . Notably, carrying IR-780 iodide within nanostructures does not require chemical bond modification, and the combination is convenient and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there have been many nanocarriers like polymers, liposomes, and inorganic molecules for encapsulating PTT agents, most of them were not efficient in co‐loading with other chemo agents. To exemplify, Caixia Yue et al., (2013) reported that the IR‐780 dye loaded tumor targeting theranostic nanoparticles for NIR imaging and PTT in which loading therapeutics agents would be difficult as the carrier is made of hydrophilic heparin .…”
Section: Resultsmentioning
confidence: 99%